2021
DOI: 10.1007/s13205-021-02860-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bacterial inoculation on co-composting of lavender (Lavandula angustifolia Mill.) waste and cattle manure

Abstract: The primary purpose of this study was to investigate the influence of Cellulomonas flavigena and Streptomyces viridosporus, as a bacterial inoculant, on the compostability of post-extraction lavender waste. The major physicochemical, microbiological, and biological properties of the composting materials were monitored for 161 days. The technology developed was shown to improve the compostability of recalcitrant herbal residues. The use of lavender waste beneficially affected the composting process by extending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…Herbal waste can also be managed by composting [38][39][40]. According to Zhou et al [41,42] and Greff et al [43], co-composting with herbal wastes increases the rate at which organic matter (OM) is degraded by microorganisms and leads to the production of high-quality compost with antipathogenic properties. Greff et al [43] investigated the influence of Cellulomonas favigena and Streptomyces viridosporus bacterial inoculants on the compostability of post-extraction lavender waste and found that lavender waste enhanced the composting process by extending the thermophilic phase, accelerating OM degradation, and increasing the viable counts of beneficial microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal waste can also be managed by composting [38][39][40]. According to Zhou et al [41,42] and Greff et al [43], co-composting with herbal wastes increases the rate at which organic matter (OM) is degraded by microorganisms and leads to the production of high-quality compost with antipathogenic properties. Greff et al [43] investigated the influence of Cellulomonas favigena and Streptomyces viridosporus bacterial inoculants on the compostability of post-extraction lavender waste and found that lavender waste enhanced the composting process by extending the thermophilic phase, accelerating OM degradation, and increasing the viable counts of beneficial microorganisms.…”
Section: Introductionmentioning
confidence: 99%